1986
DOI: 10.1002/1097-0142(19860901)58:5<1158::aid-cncr2820580530>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Risk of second malignancy after cancers of the renal parenchyma, renal pelvis, and ureter

Abstract: Risk of second primary malignancy was assessed in a population-based survey of persons who developed cancers of the renal parenchyma, renal pelvis, or ureter in Connecticut during the period 1935-1982. Among 4176 patients with a first primary tumor of the renal parenchyma, a second cancer was reported in 219 (5%), yielding a small but significantly elevated relative risk (RR) of 1.2, which reflects excesses for cancers of the bladder, kidney, and lymphatic-hematopoietic system. Among 939 patients with a first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
1
2

Year Published

1988
1988
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 10 publications
3
14
1
2
Order By: Relevance
“…The lower than expected rates of second primary lung cancer among patients included in this study are consistent with prior reports [10–12, 25]. Possible explanations for this finding could be that the survival of patients with an aggressive renal cortical neoplasm might be not long enough to allow for the development of a second smoking-related primary malignancy, or that these patients died of a smoking-related comorbidity before developing lung cancer.…”
Section: Discussionsupporting
confidence: 91%
“…The lower than expected rates of second primary lung cancer among patients included in this study are consistent with prior reports [10–12, 25]. Possible explanations for this finding could be that the survival of patients with an aggressive renal cortical neoplasm might be not long enough to allow for the development of a second smoking-related primary malignancy, or that these patients died of a smoking-related comorbidity before developing lung cancer.…”
Section: Discussionsupporting
confidence: 91%
“…Lastly, we want to point out the issue of subsequent malignancies in nephrectomized patients. Second primary cancers were reported to have developed in approximately 7% of patients successfully treated for RCC 16 . The present study also showed that 10 of 289 (3.5%) patients with no other malignancies at kidney operation experienced subsequent malignancies.…”
Section: Discussionsupporting
confidence: 72%
“…An analysis of the Connecticut Tumor Registry showed a greater risk of prostate cancer after diagnosis of an initial cancer of the kidney, renal pelvis or ureter (SIR 1.5, P < 0.05, 22 059 person‐years) [3]. Analysis of these data showed that the incidence of prostate cancer after renal parenchymal cancers was only increased during the first year after diagnosis, while there was a more sustained increase with tumours of the renal pelvis and collecting system [4]. Men with an initial diagnosis of prostate cancer had no additional risk of developing cancer of the kidney, renal pelvis or ureter (SIR 1.1, not significant, 70 358 person‐years) [12].…”
Section: Discussionmentioning
confidence: 99%